2015
DOI: 10.5713/ajas.14.0960
|View full text |Cite
|
Sign up to set email alerts
|

The Technical and Financial Effects of Parenteral Supplementation with Selenium and Vitamin E during Late Pregnancy and the Early Lactation Period on the Productivity of Dairy Cattle

Abstract: This study aimed to determine the effects of parenteral selenium (Se) and vitamin E supplementation on economic impact, milk yield, and some reproductive parameters in high-yield dairy cows in the dry period and in those at the beginning of lactation. At the beginning of the dry period, cows (n = 323) were randomly divided into three groups as follows: Treatment 1 (T1), Treatment 2 (T2), and Control (C). Cows in group T1 received this preparation 21 days before calving and on calving day, and cows in group T2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
7
1
1
Order By: Relevance
“…Negative energy balance is associated with the diet deficiencies in trace elements (i.e., selenium, iron, copper, zinc, cobalt, chromium), amino acids (i.e., lysine, L-histidine), and vitamins (i.e., A, C, E, β-carotene, lycopene), which lead to immunosuppression at cellular and humoral level during onset of lactation, consequently increasing susceptibility to infections [46,56]. Therefore, proper management of diet during transition period such as supplementation of vitamin E and zinc, is critical to prevent mastitis infection and to increase lactation [57,58].…”
Section: Host Factormentioning
confidence: 99%
“…Negative energy balance is associated with the diet deficiencies in trace elements (i.e., selenium, iron, copper, zinc, cobalt, chromium), amino acids (i.e., lysine, L-histidine), and vitamins (i.e., A, C, E, β-carotene, lycopene), which lead to immunosuppression at cellular and humoral level during onset of lactation, consequently increasing susceptibility to infections [46,56]. Therefore, proper management of diet during transition period such as supplementation of vitamin E and zinc, is critical to prevent mastitis infection and to increase lactation [57,58].…”
Section: Host Factormentioning
confidence: 99%
“…The result of the current meta-analysis showing a tendency for higher MY is consistent with the unclear trend of the vitamin E supplementation on the milk production performance. For example, several studies (Bayril et al, 2015;Schäfers et al, 2017;Vasiľ et al, 2017) reported increased MY in cows treated with vitamin E, whereas other studies did not report a beneficial effect of vitamin E administration on milk production at levels higher than current NRC (2001) recommendations (Bourne et al, 2008;Anwar et al, 2014;Vasiľ et al, 2017). Positive effects of vitamin E supplementation can be explained by the fact that prepartum vitamin E supplementation may increase DMI through increased glucose availability and levels, leading to increasing nutrient availability for milk synthesis (Chandra et al, 2013).…”
Section: Milk Colostrum and Blood Variablesmentioning
confidence: 99%
“…Several other factors may affect vitamin E availability and its efficiency in animals, including source of the vitamin E active substance, other nutrients in feeds (Campbell and Miller, 1998;Chandra et al, 2014), timing, inclusion of Se (Aréchiga et al, 1994), variation in vitamin E content of the basal ration (Lindqvist et al, 2011), and method of administration (e.g., ruminal pellets or premixes in diet, or even i.v., s.c., and i.m. injection; Aréchiga et al, 1994;Bayril et al, 2015), applied over different time spans and frequencies with cows fed different diets and levels of production.…”
Section: Introductionmentioning
confidence: 99%
“…This type of supplementation also contributed to higher daily weight gain in heifers [ 17 ] and steers [ 18 ], improved health and antioxidant status and reduced bacterial infections in newborn calves [ 19 ]. Likewise, the use of injectable vitamin E and Se in prepartum dairy cattle enhanced antioxidant capacity [ 20 ] and decreased the incidence of postpartum mastitis [ 21 ]. However, average weight gain (AWG) was not improved in weaning calves [ 22 ].…”
Section: Introductionmentioning
confidence: 99%